Pengaruh Kualitas Pelayanan Pajak, Kesadaran Wajib Pajak, dan Sanksi terhadap Keputusan Wajib Pajak Orang Pribadi - Kayla Asyifa Wirawan; Devyanthi Sjarif (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the influence of tax service quality, taxpayer awareness, and tax sanctions on individual taxpayer compliance at KPP Pratama Majalaya. The research is based on the declining trend of annual tax return filing ratios, despite an increase in the number of taxpayers. A quantitative approach was used with descriptive and verificative methods. A total of 100 respondents were selected through simple random sampling. Data were collected using questionnaires and analyzed with multiple linear regression. The results show that tax service quality, taxpayer awareness, and tax sanctions have a positive and significant effect on taxpayer compliance, both partially and simultaneously. The model explains 33.1% of the variation in compliance levels. These findings highlight the importance of service improvement, ongoing tax education, and the fair and firm implementation of sanctions. The study offers strategic recommendations for KPP Pratama Majalaya to develop compliance-enhancing policies that are tailored to the socio-economic characteristics of local taxpayers.